Environmental variability shapes the representational format of cultural learning - Xavier Roberts-Gaal; Marija Bolic; Fiery A. Cushman (Proceedings of the National Academy of Sciences, 2025)
Cumulative culture requires learning mechanisms that are both efficient and flexible in the face of environmental change. We examine models of this learning mechanism that emphasize teaching what to do (causally opaque procedures) and those that foreground what to aim for and why (goals and causal reasoning). Learning procedures is cheap but inflexible; learning goals is more flexible to changing circumstance, but requires expensive individual learning about how to achieve them. In an iterated learning experiment, we demonstrate that cultural learning adapts in precisely this way: Microcultures more often instruct future generations to follow procedures when the world is stable, but they tend to share information about valuable outcomes and causal relations when the world is variable.